THE INFLUENCE OF DIGITAL MARKETING CAPABILITY AND BEHAVIORAL CUSTOMER RELATIONSHIP MANAGEMENT ON INCREASING SALES OF MSMEs: EMPIRICAL STUDY IN SURAKARTA CITY - Syihabuddin, Muhammad; Wulandari, Astuti (Program Studi Magister Manajemen Universitas Advent Indonesia, 2025)
This study aims to analyze the influence of Digital Marketing Capability and Behavioral Customer Relationship Management (BCRM) on the sales performance of Micro, Small, and Medium Enterprises (MSMEs) in Surakarta, Indonesia. The research is motivated by the increasing need for MSMEs to adapt to digital transformation and to understand customer behavior in order to remain competitive. A quantitative approach was employed using survey data from 150 MSME owners, and the data were analyzed using multiple linear regression. The results show that both Digital Marketing Capability and Behavioral CRM have a positive and significant effect on sales improvement. Behavioral CRM has a stronger influence compared to Digital Marketing Capability, indicating that marketing strategies based on customer behavioral insights yield better performance outcomes. These findings are consistent with the Resource-Based View and Relationship Marketing Theory, and support previous studies emphasizing the importance of technology integration and customer relationship strategies. The managerial implication is that MSMEs should enhance their digital marketing capabilities and develop CRM systems that effectively utilize customer behavioral data. The study is limited to a specific geographic area and uses cross-sectional data; thus, future research is encouraged to adopt longitudinal designs and expand the study scope.